Matching employment opportunities and expectations : a programme of action for Ceylon - International Labour Office (Geneva : International Labour Office, 1971)
One of the messages that ring quite clearly through the pages of the report is that there are no soft options left in Ceylon for the government to take. Assets created in the past have been used up, opportunities have been missed and the Ceylonese economy is currently caught in the Malthusian box with a superimposed, lavishly programmed welfare state. The I. L. O. team makes many useful suggestions for expanding the industrial output, creating employment opportunities, reforming the educational system, realigning the pay structures, land reforms, and many others. But the crucial reform and the most difficult to consider is the modification of what the I. L. O. team has termed as the benefit compliance politics that is not considered adequate to meet the challenges of the seventies. The team has hopefully suggested "a leadership cooperation pattern to replace the benefit compliance politics" (p 162).
Includes bibliographical references.
rpm 17/04/2018
Loans
Keywords: Manpower policy; Unemployed